Effects of diet form and fiber withdrawal before marketing on growth performance of growing-finishing pigs - Nemechek, J.E.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 288 pigs (PIC 327 × 1050, initially 109.3 lb BW) were used in an 81-d trial to determine the effects of diet form and fiber (from dried distillers grains with solubles [DDGS] and wheat middlings) withdrawal before harvest on growth performance of growing-finishing pigs. Treatments were arranged in a 2 × 3 factorial with the main effects of diet form and dietary fiber feeding regimen. The 2 diet forms were meal or pellet. The 3 fiber feeding regimens were (1) low dietary fiber (corn-soybean meal–based diets) from d 0 to 81, (2) high dietary fiber (30% DDGS and 19% wheat midds) from d 0 to 64 followed by low fiber from d 64 to 81 (fiber withdrawal), and (3) high dietary fiber from d 0 to 81.
Keywords: Swine; DDGS; Diet form; Pellet; Finishing pig; Wheat middlings